Intrinsic connectivity network disruption in progressive supranuclear palsy. Issue 5 (27th March 2013) - Gardner, Raquel C.; Boxer, Adam L.; Trujillo, Andrew; Mirsky, Jacob B.; Guo, Christine C.; Gennatas, Efstathios D.; Heuer, Hilary W.; Fine, Eric; Zhou, Juan; Kramer, Joel H.; Miller, Bruce L.; Seeley, William W.
<x xml:space="preserve">Abstract</x> Objective Progressive supranuclear palsy (PSP) has been conceptualized as a large‐scale network disruption, but the specific network targeted has not been fully characterized. We sought to delineate the affected network in patients with clinical PSP. Methods Using task‐free functional magnetic resonance imaging, we mapped intrinsic connectivity to the dorsal midbrain tegmentum (dMT), a region that shows focal atrophy in PSP. Two healthy control groups (1 young, 1 older) were used to define and replicate the normal connectivity pattern, and patients with PSP were compared to an independent matched healthy control group on measures of network connectivity. Results Healthy young and older subjects showed a convergent pattern of connectivity to the dMT, including brainstem, cerebellar, diencephalic, basal ganglia, and cortical regions involved in skeletomotor, oculomotor, and executive control. Patients with PSP showed significant connectivity disruptions within this network, particularly within corticosubcortical and cortico‐brainstem interactions. Patients with more severe functional impairment showed lower mean dMT network connectivity scores. Interpretation This study defines a PSP‐related intrinsic connectivity network in the healthy brain and demonstrates the sensitivity of network‐based imaging methods to PSP‐related physiological and clinical changes. Ann Neurol 2013;73:603–616